PERANCANGAN APLIKASI PRESENSI KELAS DENGAN MENGGUNAKAN METODE PENGENALAN WAJAH SECARA KOLEKTIF - Richard Sam; Syaiful Rahman; Junaedy (JTRISTE, 2018)
The purpose of this research is to design a class presension application using Collective Facial Recognition using Haar-Cascade methods. The presension problem nowadays is really worrying. Lately, there’s a lot of presension problem, either from college students or from another acamedic instances. Which is why the author is trying to design a presension application that implements facial recognition system in classrooms to deal with this presension problem. The author uses Microsoft Visual Studio 2010 to design and create this application. The result of this research is the author managed to design and create the presension application using facial recognition with Visual Studio 2010 with accuracy rate along 71%.